Governing Collaborative Healthcare Improvement: Lessons From an Atlantic Canadian Case - Meghan Rossiter; Jennifer Verma; Jean-Louis Denis; Stephen Samis; Richard Wedge; Chris Power (Kerman University of Medical Sciences, 2017)
The Atlantic Healthcare Collaboration for Innovation and Improvement in Chronic Disease (AHC) Quality Improvement Collaborative (QIC) in Eastern Canada provided an approach to spur system-level reform across multiple health systems for patients and families living with chronic disease. Developed and led by senior executives with a unique governance approach and involving clinical front-line teams, the AHC serves as a practical example of leadership creating and driving momentum for achieving success in collaborative health system improvements.